Fabrication of amorphous silicon microgap structure for energy saving devices - Dhahi, T.H.S.; Uda, Hashim, Prof. Dr.; Md. Eaqub, Ali; Nazwa, T. (Sains Malaysiana., 2013)
Link to publisher's homepage at http://www.ukm.my/jsm/